Influence of structural disorder on the photoluminescence emission of PZT powders - Longo, Elson [UNESP]; de Figueiredo, A. T. [UNESP]; Silva, M. S.; Longo, V. M.; Mastelaro, V. R.; Vieira, N. D.; Cilense, M. [UNESP]; Franco, R. W. A.; Varela, José Arana [UNESP] (Amer Chemical Soc, 2008)
Intense and broad visible photoluminescent (PL) band was observed at room temperature in disordered Pb(Zr(0.53)Ti(0.47))O(3) powders. Structural order-disorder was evaluated by different methods. XANES results pointed to the presence of different coordination modes of disordered Ti powders, and in the ordered sample the local structure around titanium atoms is characteristic of the structurally ordered PZT with only TiO(6) units. Only samples containing simultaneous structural order and disorder in their network present the intense visible PL emission at room temperature.